Failures of Flexibility: How Perceived Control Motivates the Individualization of Work–Life Conflict. (January 2020) - Wynn, Alison T.; Rao, Aliya Hamid
Firms have increasingly used flexibility policies to facilitate work–life balance, yet existing research shows that employees are stigmatized for using these seemingly beneficial policies. In this article, the authors identify perceived control, that is, the sense of control employees feel they have over managing their work–life conflicts, as a key factor in their avoidance of flexibility policies. Through 50 in-depth interviews with management consultants from five firms, the authors find that employees frame managing their work–life conflicts as a test of their professional skills, emphasize their "natural" suitability for the consulting industry, use choice rhetoric to reframe oppressive work demands as personal choices, and accentuate their ability to exit the consulting industry if they are unable to manage their work–life balance independently. Empirically, this study provides a fuller explanation for the pervasive avoidance of flexibility policies and expands on prior explanations that focus on flexibility stigma.